The Mechanism For Electing The Deputy Prime Minister In The Constitution Of The Republic Of Iraq For The Year 2005 And Similar Constitutions - Mohammed Hashem Mohammed Al-Hussainawi (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The position of the Prime Minister (PM) in Iraq is the head of the Iraqi government and the Iraqi Council of Ministers and is represented as the direct executive responsible for the general policy of the state and the commander in chief of the Iraqi armed forces. The PM is assigned by the President of the Republic and the candidate of the most numerous parliamentary bloc in the parliamentary systems, as he forms the Council of Ministers within fifteen days from the date of the election of the President of the Republic. The problem of this study lies in the constitutional and legal absence, which takes it upon itself to refer to this important position, and defines its competence and powers. The most important problem of this study, including, the legal and constitutional adaptation to the position of Deputy Prime Minister (DPM), whether at the national, global, and European levels. Besides, whether is the position of the PDM considering a public servant or assigned to public service. Obviously, from imposing the possibility on the Iraqi and international levels of most foreign countries that this problem will have a number of results about this characterization. In this research, the researcher used the analytical method, where the research was dealt with in two topics, introducing the Deputy Prime Minister, and the second topic was devoted to the mechanism of electing the Deputy Prime Minister.